Crisis resilience: Humanitarian response and anticipatory action - Kurdi, Sikandra; Ruckstuhl, Sandra (International Food Policy Research Institute, 2023)
In human, economic, and environmental terms, the total cost of disaster and crisis response is extremely high, and the disastrous combination of the food price crises coming on the heels of the COVID-19 pandemic and natural calamities is straining public budgets and squeezing financial options. In 2020, private and public losses from weather-related disasters alone exceeded a total of US$258 billion globally — 29 percent above the 2001–2020 average — making it the fifth costliest year on record, and rising temperatures are expected to bring even more frequent and severe extreme weather events. At the same time, conflict has become a leading contributor to humanitarian crisis situations — as seen most recently with the food and energy crises precipitated by the Russia-Ukraine war and refugee flows driven by the Syrian civil war.